Belgesel ile kurmaca kaynaştırılabilir mi? Kırılma - Morva, Ahsen Deniz (My University, 2009)
Belgesel ile kurmaca film üzerine yapılan tartışmalar sinema tarihiyle yaşıttır. Sinemanın belge filmlerle başlaması, sinema sanatının gelişmesiyle belgesel filmlerin üretilmesi ve filmin üretim sürecinin kendisi bu tartışmayı her dönem gündemde tutmuştur. Belgesel ve kurmaca film arasındaki sınırlar çizilmeye çalışılmış ancak üretilen filmlerin çeşitliliği herkesin üzerinde uzlaştığı bir belgesel film tanımı yapmayı güçleştirmiştir. Günümüzde ise belgesel ve kurmaca film arasındaki çizgi gerçekten çok incedir. Kırılma adlı proje iki kategori arasındaki sınırın tartışmalı olduğu bu alana eğilmektedir. Belgesel ve kurmaca kaynaştırılabilir mi? sorusu sorularak belgesel ve kurmaca görüntülerin birlikte kullanıldığı ama bu görüntülerin yan yana, birlikte değil iç içe geçtiği bir yöntem denenmektedir. Yarı belgesel yarı kurmaca film yapma amacı taşımadan, seyircinin kafasında belgesel ve kurmaca görüntülerin nerede başlayıp nerede bittiği sorusunu sordurmadan belgesel ve kurmaca görüntülerin kaynaşmasının nasıl mümkün olduğu araştırılmıştır. Sorunun araştırılacağı filmin teması insanlık tarihi kadar eski, çok boyutlu ve katmanlı bir olgu olan aşktır. ‘Aşk cam gibidir, kırılırsa eskisi gibi olmaz’ temalı kısa metrajlı filmde aşk olgusunun cam sanatı ile birlikte düşünülmesi hedeflenmiştir. Cam yapımı ve aşk ilişkisi arasındaki benzerlik; kaynaşmanın aşkın ve camın oluşumundaki belirleyici rolü filmin biçimine esin kaynağı olmuştur. Filmde cam yapımı görüntüleri aşk ilişkisi için yazılan kurmaca sahnelerle birlikte kurgulanmış; cam yapımı görüntüleri belgesel, aşk ilişkisi de kurmaca görüntülerle anlatılmaya çalışılmıştır. Filmde belgesel olan cam yapım görüntüleri, cam yapımının belgelenmesi ve cam yapımı hakkında bilgi vermenin dışında aşk olgusunu da açıklayan bir işleve sahiptir. Cam yapımı görüntüleri nitelik değiştirerek aşk olgusuna anlam katmıştır. Belgesel görüntüler eğretileme olarak kullanılarak belgesel ve kurmaca kaynaştırılmıştır.

The discussion between documentary and fiction film is as old as cinema itself. Because of the beginning of the cinema history with document films, the production of documentaries after the improvement of cinema art and the production process of film making these discussions keep on. Film theorists tried to draw the line between documentary and fiction film, however, the variety of films makes important difficulties on the definition of documentary film that everyone agrees on. Nowadays, the line between documentary and the fiction film is tenuous indeed. The project, titled ‘Kırılma’ is focuses on the territory that the line between two categories are controversial. Could documentary and fiction films be combine together? With this question, what I am attempting is on the one hand, the images of documentary and fiction are used together and on the other hand these images are not used side by side, but one within the other. Not having the aim of making a docufiction, how is it possible that the combination of the images of documentary and fiction is researched, without making any questions on the audience that where the images of documentary and fiction start and end. The theme of the film, that is questioning, is as old as humanity, and has lots of dimensions is love. In the short length movie, that the theme is ‘Love is like glass, when it is broken it won’t be as before’ the main goal is thinking the issue of love and the art of glass together. The similarity between the production of glass and the relation in love; the determinant role of the combination in the love and the creation of glass, was the motivation of the style of the film. In the film, the images of the producing of glass is edited with the fiction scenes that was written for the relation of love. The images of the producing of glass is tried to be expressed with the images of documentary, and the relation of love is expressed with the images of fiction part of the film. The documentary of the images of the producing of glass has also the function of the documentation of the glass producing and giving the information on glass producing in addition to the expression of love. The images of glass producing has changed its property and give a meaning on the issue of love. The images of the documentary used as a metaphor to combine the documentary and the fiction.
Keywords: Belgesel; Beyaz Perde; Sinema